2016
DOI: 10.1038/sc.2016.62
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for spinal rehabilitation professionals regarding sexual education needs and preferences of people with spinal cord dysfunction: a mixed-methods study

Abstract: There was very low satisfaction with sexuality education during rehabilitation. Our findings highlight the scope and directions for improving the sexual education and information given to people with both SCDys and SCI during rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 29 publications
1
34
0
2
Order By: Relevance
“…1 However, persons with SCI or SCD are often dissatisfied about the education and the treatment they receive regarding sexual concerns, 2 and this lack of care may lead to a decrease in patient's participation in sexual activity and sexual satisfaction. Thus, it is important for clinicians to take sexual concerns into account and address them as they work to engage in patientcentered care.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, persons with SCI or SCD are often dissatisfied about the education and the treatment they receive regarding sexual concerns, 2 and this lack of care may lead to a decrease in patient's participation in sexual activity and sexual satisfaction. Thus, it is important for clinicians to take sexual concerns into account and address them as they work to engage in patientcentered care.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with SCI express dissatisfaction with sexual education after injury. 12 Akman reported that Turkish men with SCI preferred to have sexual education given by physicians after the completion of the rehabilitation period, yet in that study, only 8.5% of patients received sexual education after injury. 15 Though no consensus exists on the timing, methods and details of sexual education after traumatic SCI, we believe that a protocol for this aspect of management is warranted.…”
Section: Discussionmentioning
confidence: 89%
“…11 Historically, education in sexuality was rarely carried out during rehabilitation after SCI due to lack of prioritizing these complications or physician discomfort. 12 We sought to determine the frequency and severity of erectile and ejaculatory dysfunctions and their correlates in a sample of men with SCI. We also sought to determine the fertility desires and treatment options offered for sexual and fertility enhancement in these men.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated the sexual education and rehabilitation in patients with SCI can improve overall satisfaction and quality of life. 33 …”
Section: Discussionmentioning
confidence: 99%